Latin Literature. (October 2019) - Whitton, Christopher
Abstract : How did the Romans do philology? Think in terms of the Latin language, and Varro's De lingua Latina, Caesar's De analogia, or Quintilian's chapters on grammar might come to mind. Think of commentary on texts, and names like Servius, Asconius, and Porphyrio won't be far away. But few of us, it's probably fair to say, could claim a deep acquaintance with all of those, and still fewer have acquired much sense of the broader picture – and it is broad – of ancient scholarship in and on Latin. Cue James Zetzel's Critics, Compilers, and Commentators, a massive and remarkable study of Roman philology from antiquity into the early Middle Ages.